1975
DOI: 10.1083/jcb.66.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and purification of polymerized actin from sea urchin egg extracts.

Abstract: Isotonic extracts of the soluble cytoplasmic proteins of sea urchin eggs, containing sufficient EGTA to reduce the calcium concentration to low levels, form a dense gel on warming to 35 40~ Although this procedure is similar to that used to polymerize tubulin from mammalian brain, sodium dodecyl sulfate-polyacrylamide gel electrophoresis shows this gel to have actin as a major component and to contain no tubulin. If such extracts are dialyzed against dilute salt solution, they no longer respond to warming, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
145
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(151 citation statements)
references
References 36 publications
6
145
0
Order By: Relevance
“…Gelation of cytoplasmic extracts has been related to actin (23) or interactions of actin and other proteins (13,35,37) in at least four different systems. In the macrophage system (35), gelation is also inhibited by >1 /xM CB* (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelation of cytoplasmic extracts has been related to actin (23) or interactions of actin and other proteins (13,35,37) in at least four different systems. In the macrophage system (35), gelation is also inhibited by >1 /xM CB* (11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several laboratories have discovered that gelation of suitable cell extracts can be related to actin (23), actin and a high molecular weight protein (HMWP) (35, 37) or actin, a HMWP, and a third protein (13). Knowing that CB disrupts the contractile ring (which contains actin) (28,29) and binds to both high and low affinity sites in HeLa cells (15), it seemed of interest to test whether CB affected the formation and composition of gel in HeLa cell extracts.…”
mentioning
confidence: 99%
“…HMWPs that interact with actin have been implicated in cytoplasmic consistency changes (3,10,11,(13)(14)(15)19). Macrophage ABP and smooth muscle filamin have been isolated and appear to be similar (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Because the ratios of actin to myosin are an order of magnitude higher in nonmuscle cells than in muscle cells (1, 2), functional interactions of actin with proteins other than those involved in the regulation of actomyosin ATPase have also been proposed. Kane showed that actin in sea urchin egg extracts gelled upon warming to 370C (3). Two polypeptides, of molecular weight 58,000 and 220,000, appeared to be involved in the process.…”
mentioning
confidence: 99%
“…Fascin was first identified in sea-urchin egg extracts [14] and was identified in human HeLa cells in 1985 [15]. It is one of the actin cross-linking binding proteins required for the formation of actin-based cell-surface protrusions and increased cell motility in various transformed epithelial cells [16,17].…”
Section: Introductionmentioning
confidence: 99%